2014
DOI: 10.1016/j.childyouth.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of family assets and debt on college graduation

Abstract: This study examines the influence of family financial assets and debt, both measured during the time of youth's college enrollment, on the chances of college graduation. Data come from the National Longitudinal Survey of Youth. Results from analyses controlling for a number of student, parental, and institutional characteristics indicate that family assets are positively related to the chances of college graduation among White and Black students; family debt is negatively associated with the odds of college gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Similar to the disparities in other SES indicators, educational attainment varies by race/ethnicity, which may be largely impacted by financial difficulties. While family assets positively impact the chances of college graduation for AA and White students, family debt is more detrimental to AA students likelihood of graduating than White students (39). Research from a national sample of low-and middle-income households found that, for AA students, the odds of student loan indebtedness is twice as high as it is for White students, and this disparity persists even after accounting for degree completion and other SES factors (40).…”
Section: Demographic Social and Behavioral Factorsmentioning
confidence: 99%
“…Similar to the disparities in other SES indicators, educational attainment varies by race/ethnicity, which may be largely impacted by financial difficulties. While family assets positively impact the chances of college graduation for AA and White students, family debt is more detrimental to AA students likelihood of graduating than White students (39). Research from a national sample of low-and middle-income households found that, for AA students, the odds of student loan indebtedness is twice as high as it is for White students, and this disparity persists even after accounting for degree completion and other SES factors (40).…”
Section: Demographic Social and Behavioral Factorsmentioning
confidence: 99%
“…Numerous researchers have found a relationship between parents' income or other economic resources and their children's educational attainment (Akee et al, 2010;Acemoglu & Pischke, 2001;Cabrera & La Nasa, 2002;Gerardi, 1996;Johnson, 2008;Marr et al, 2015;Nam & Huang, 2009;Pelavin & Kane, 1990;Rylance, 1997;Zhan & Lanesskog, 2014). In one study, a 10% increase in one's family income was associated with a 1.4% increase in the likelihood of attending a 4-year college (Acemoglu & Pischke, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study aims to examine the influence of family financial assets during the time of student"s college enrollment has been conducted by M. Zhan and D. Lanesskog [26]. The data is gathered from the National Longitudinal Survey of Youth.…”
Section: Literature Reviewmentioning
confidence: 99%